Indonesian Muslims and Christians positions during a terror attack : analysis on Facebook posts #prayforsurabaya - Supardi, Achmad (Penerbit Universiti Kebangsaan Malaysia, 2022)
Indonesians and the world were shocked by a series of terror attacks in Surabaya, East Java, 13-14 May 2018. As predicted, Indonesians went online to share their mourning and condemnation of the attacks. Facebook posts with the hashtag #prayforsurabaya are places for online users to express their thoughts. This research employed content analysis and Leximancer’s thematic analysis to investigate three research questions: the dominant themes among the Facebook users’ responses as shown in #prayforsurabaya, how Facebook users position the terror attacks and religious identity within the Indonesian and global socio-political dynamics and presumptions Facebook users have regarding inter-groups and citizen-government relations. This study shows that Facebook users mostly went to two different discursive activisms through which both Indonesian Christians and Muslims perceived themselves as the victim of the terror attack. Christians regarded themselves as the direct target of the attack, while Muslims perceived themselves as the victim of slander and discursive hijacking. #Prayforsurabaya also hosts counter-frames, mainly to challenge the identification of Islamic teaching as the breeder of terrorism and defy the burqa as one denominator of terrorism. Most Facebook users also engaged in corrective action against the circulation of pictures and videos of terror victims and against the idea that terror attack was merely the government’s effort to divert people’s attention from criticizing their allegedly poor performance.